Morphology of the nymphoid replacement reproductives in the neotropical termite Armitermes euamignathus (Isoptera, Termitidae, Nasutitermitinae) - Costa-Leonardo, A. M.; Barsotti, R. C.; Soares, H. X. (Wiley-Blackwell, 1999)
Numerous nymphoid reproductives were found in three field nests of Armitermes euamignathus collected in Brazil. We report here a morphological description and a biometric study of these individuals. Nymphoid replacements displayed narrow wing buds when compared with those present in nymphs from the three last instars. Thorax morphology of the nymphoids was similar to the penultimate nymphal instar (N4) or to the ultimate nymphal instar (N5), and their origin from these instars of nymphs is discussed. All the nymphoids had eyes, ocelli, and 15 antennal segments. The nymphoid females from nest 1 had different grades of physogastry and royal fat body. The nymphoid females from nests 2 and 3, the nymphoid males from all nests, and the primary king from nests 2 acid 3 had a common fat body, which is similar to that present in alates. The ovaries and the testes of nymphoids were fully mature and the corpora allata larger than those in imagoes. The mandibular glands were also enlarged in nymphoids but the tergal glands were absent. (C) 1999 Wiley-Liss, Inc.
Keywords: nymphoids; replacement reproductives; termite; Isoptera; Armitermes